COMPUTATIONAL FLUID DYNAMICS ANALYSIS OF A SHELL-AND-DOUBLE CONCENTRIC TUBE HEAT EXCHANGER - Nofrizalidris Darlis; Kahar Osman; S.M. Shahril; M.K.R Hashim; A.M.N. Bariah; Ummikalsom Abidin, (Applications of Computational Fluid Dynamics in Mechanical Engineering (Series 4), 2025)
Shell-and-tube heat exchangers (STHEX) have been used for several decades. Conventionally, to increase the thermos-hydraulic performance of classical heat exchangers, the overall length of tubes has to be increased. This contributes to major disadvantages in terms of classical heat exchangers’ design, particularly considering the economic aspect. In this study, the thermo-hydraulic performance analysis of a shell-and-double concentric tube heat exchanger (SDCTHEX) is carried out using commercially available Computational Fluid Dynamics (CFD) software ANSYS FLUENT. The results show that the average percentage increase in overall heat transfer rate per overall pressure drop of SDCTHEX, with inner tube diameter equal to 8/12 mm/mm, is nearly 343% higher than that of STHEX, while the total friction power expenditure of SDCTHEX is reduced by around 85.5% as compared to that of STHEX. Also, the overall heat transfer rate per overall pressure drop of SDCTHEX is sensitive to inner tube diameter. It is found that U=DP for the mass flow rate of 22.5 kg/s is maximum and found to be about 400% higher at inner tube diameter of 12/16 mm/mm with respect to the STHEX. The results of simulation present that, the SDCTHEX has a higher heat transfer performance while maintaining a lower pressure drop.Keywords: Shell-and-tube heat exchangers, CFD, thermo-hydraulic